Noise reduction approach for Arabic phonemes articulated by Malay speakers - Almisreb A.A.; Tahir N.M.; Abidin A.F.; Din N.M. (Institute of Electrical and Electronics Engineers Inc., 2023)
Speech recognition; Arabic. Malay; Computational time; Gamma correction; Gamma function; Modified equation; Speech segmentation; Speech waveforms; Zero crossing rate; Signal processing